A selective forwarding technique for data dissemination in vehicular ad hoc networks based on traffic parameters. (17th November 2020) - Pradhan, Rangaballav; De, Tanmay
In this work, a novel data dissemination technique is proposed based on the selective forwarding mechanism. Various network parameters such as node density, inter-vehicular distance and time to leave are considered for choosing the appropriate relaying node out of a set of one hop neighbouring nodes of the sender. Veins, a simulation framework combining the power of OMNet++ and SUMO, is used to simulate and test the proposed approach. Simulation results are obtained by considering various performance metrics and the effectiveness of the method is justified by comparing with two existing methods namely selective flooding and unidirectional flooding. The analysis of these results showed that the proposed method has a higher packet delivery ratio and coverage rate with a throughput surplus of 15% and 29% more than that of selective and unidirectional flooding respectively. It also has a minimum delay and a lower collision rate than the two flooding-based approaches.